2016
DOI: 10.1016/j.atherosclerosis.2015.10.103
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism in patients infected with Nef-deficient HIV-1 strain

Abstract: Background HIV protein Nef plays a key role in impairing cholesterol metabolism in both HIV infected and bystander cells. The existence of a small cohort of patients infected with Nef-deficient strain of HIV presented a unique opportunity to test the effect of Nef on lipid metabolism in a clinical setting. Methods Here we report the results of a study comparing six patients infected with Nef-deficient strain of HIV (ΔNefHIV) with six treatment-naïve patients infected with wild-type HIV (WT HIV). Lipoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The Nef/ACOT8 association may also ensure an efficient HIV-1 virions budding, modifying the composition of membrane lipids. Interestingly, it has been reported that Nef plays a significant role in pathogenesis of lipid-related metabolic complications of HIV-1 infection 44 . However, whether Nef has any need to be localized to peroxisomes is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The Nef/ACOT8 association may also ensure an efficient HIV-1 virions budding, modifying the composition of membrane lipids. Interestingly, it has been reported that Nef plays a significant role in pathogenesis of lipid-related metabolic complications of HIV-1 infection 44 . However, whether Nef has any need to be localized to peroxisomes is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection and antiretroviral therapy are both associated with significant disturbances in systemic metabolic regulation, including lipids, which play a central role in the host immune response, as previously reviewed ( Willig and Overton, 2016 ). While dyslipidemia is a recognized risk factor for age-related diseases, such as cardiovascular disease, only a handful of studies have investigated the plasma lipid profiles in HIV infection, and these have focused on cardiovascular risk prediction ( Wong et al, 2014 , Low et al, 2016 ). There is a paucity of data reflecting the association between dysregulated lipid metabolism with frailty.…”
Section: Introductionmentioning
confidence: 99%
“…They were compared with patients infected with Nef-positive (WT) HIV-1 strain ( n =6) and six HIV negative subjects selected from a group of healthy volunteers. Description of the patients is presented in the main paper [1] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The data can be used to evaluate cardiovascular risk in HIV disease and to assess the role of nef in HIV-induced disturbances in systemic lipid metabolism. The full impact of nef deficiency on lipid and lipoprotein metabolism in HIV-infected patients is presented in the accompanying study “Lipid Metabolism in Patients Infected with Nef-deficient HIV-1 Strain” [1] .…”
mentioning
confidence: 99%